2007
DOI: 10.1111/j.1530-0277.2007.00519.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cigarette Smoking and Family History of Alcoholism on Sweet Taste Perception and Food Cravings in Women

Abstract: Background-Despite popular beliefs that smoking affects the sensitivity and liking of sweettasting foods and beverages, few psychophysical studies have examined this phenomenon and none have taken into account the individual's family history of alcoholism (FH+), a predictor of heightened sweet preferences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
84
5
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 114 publications
(99 citation statements)
references
References 71 publications
9
84
5
1
Order By: Relevance
“…Finally, unhealthy lifestyle characteristics influence dietary intake and increase the risk of obesity (32,33); they can be considered to have a physiologic and behavioral impact on liking. Indeed, conflicting results were found with respect to smoking status (34,35), whereas a history of alcoholism or excessive alcohol intake appeared to be positively associated with sweet liking (36)(37)(38). Available studies mainly have been conducted in small samples and results are subject to caution.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…Finally, unhealthy lifestyle characteristics influence dietary intake and increase the risk of obesity (32,33); they can be considered to have a physiologic and behavioral impact on liking. Indeed, conflicting results were found with respect to smoking status (34,35), whereas a history of alcoholism or excessive alcohol intake appeared to be positively associated with sweet liking (36)(37)(38). Available studies mainly have been conducted in small samples and results are subject to caution.…”
Section: Introductionmentioning
confidence: 80%
“…Smokers and alcohol drinkers were more likely to like saltiness, whereas women smokers were less likely to like sweetness. In experimental studies, smokers had a lower liking for the sweet taste (34,54) and higher sucrose detection thresholds than never-smokers (38). One physiologic explanation for modification of taste detection is that nicotine plays a role in the modulation of taste signals (55), but we cannot explain taste specificity, i.e., the fact that smokers like more saltiness and less sweetness than nonsmokers.…”
Section: Discussionmentioning
confidence: 97%
“…22 In adults, smoking has been associated with decreased sweet preference, whereas a family history of alcoholism is associated with increased sweet preference. 23 The sucrose preference test is thus recommended as a supplemental measure for older participants, to be administered if time permits.…”
Section: Choice Of Taste Stimuli For Use Inmentioning
confidence: 99%
“…6 One experimental study reported that smokers had significantly higher liking of sweets than did never smokers. 7 Although it is speculative, it is also plausible that unhealthy behaviors (eg, substance use) could be associated with other secondary unhealthy dietary behaviors such as Correspondence: Dr Park; spark3@cdc.gov. …”
mentioning
confidence: 99%